1991
DOI: 10.1007/bf01368738
|View full text |Cite
|
Sign up to set email alerts
|

Zigarettenrauchen und psychosoziale Arbeitsbelastungen bei Besch�ftigten des mittleren Managements

Abstract: The association between psychosocial work stress and cigarette smoking is analyzed in a socioeconomically and professionally homogeneous group of 163 middle managers (40-55 years; 48.4 +/- 4.5) in a large industrial company. Psychosocial stress is defined in terms of an imbalance between effort spent and reward obtained at work. The relative risk of regular smoking is 4.34 (odds ratio after controlling for age; 95% CI 1.50-12.54) in those middle managers who suffer from a marked imbalance between effort and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…The second study to be reported was a crosssectional analysis of associations between indicators of effort-reward imbalance at work and major coronary risk factors such as hypertension, elevated fibrinogen, elevated atherogenic lipids, and smoking in a sample of male middle managers (n = 179; ages 40-55; M = 48.5 ± 4.5). This sample was remarkably homogeneous in terms of age and occupational status, and it was representative of the total group of middle managers of this age group in the enterprise (Peter, Siegrist, Stork, et al, 1991). In both studies, epidemiological and clinical information was combined with psychophysiological information derived from a standardized psychomental stress test (Klein, 1990(Klein, ,1995.…”
Section: Direct Evidencementioning
confidence: 99%
“…The second study to be reported was a crosssectional analysis of associations between indicators of effort-reward imbalance at work and major coronary risk factors such as hypertension, elevated fibrinogen, elevated atherogenic lipids, and smoking in a sample of male middle managers (n = 179; ages 40-55; M = 48.5 ± 4.5). This sample was remarkably homogeneous in terms of age and occupational status, and it was representative of the total group of middle managers of this age group in the enterprise (Peter, Siegrist, Stork, et al, 1991). In both studies, epidemiological and clinical information was combined with psychophysiological information derived from a standardized psychomental stress test (Klein, 1990(Klein, ,1995.…”
Section: Direct Evidencementioning
confidence: 99%
“…Previous ERI studies have predicted other employee behaviors such as days missed due to illness (Peter & Siegrist, 1997), smoking (Peter, Siegrist, Stork, Mann, & Labrot, 1991), and alcohol consumption (Puls, Wienold, & Blank, 1998). To date, however, the ERI outcomes reported have been limited to individual health-related concerns.…”
Section: Components Of the Effort Reward Imbalance Modelmentioning
confidence: 98%
“…The only prospective study on smoking intensity resulted in a negative finding (45). Concerning the effort-reward imbalance model, only two studies have been published, one restricted to a male sample with positive findings on smoking intensity (46) and one exploring smoking status and intensity among men and women and in which the full model was supported only among the women (23).…”
Section: The Challenge Of Mechanisms: Health Risk Behaviormentioning
confidence: 99%